COVID-19, migración externa y desplazamientos territoriales en Cuba, una mirada diferente a la población residente en la capital del país. / COVID-19, external migration and territorial displacement in Cuba, a deferential look at the population residing in the country's capital. - Antonio Aja Díaz; Arianna Rodríguez García; Marbelis Orbea López (Universidad de La Habana, 2020)
The pandemic caused by COVID-19 has had an unprecedented impact on all areas of human life, including migration and mobility. Starting from the fact that, if the epidemic is contained in one place and in others it is not very likely that it will constantly re-emerge, without a doubt, an important aspect for the gradual and effective recovery of society will be the effectiveness with the that population mobility is contained and subsequently restarted. Based on this scenario and taking into account that human mobility constitutes the main risk of importation and dissemination of the SARS-CoV-2 infection, it has been decided to carry out an analysis of the epidemiological situation and of international mobility and migration in Cuba -with emphasis on Havana- since this province is the capital of the country and the epicenter of the epidemic in the national territory. The fundamental sources of information come from the National Statistical Information System; the Ministry of Public Health; the Ministry of Labor and Social Security; the Ministry of Transport; of the Directorate of Identification, Immigration and Aliens and of information published on the website Our World in Data. / RESUMEN La pandemia causada por la COVID-19 ha tenido un impacto sin precedentes en todas las áreas de la vida humana, incluyendo las de la migración y la movilidad de la población. Partiendo del hecho de que, si la epidemia es controlada en un lugar y no en otros, es muy probable que re-emerja constantemente, sin lugar a dudas, un aspecto importante para la recuperación paulatina y efectiva de la sociedad lo constituirá la efectividad con la que se contenga y posteriormente se reinicie la movilidad poblacional. A partir de este escenario, y tomando en cuenta que la movilidad humana constituye el principal riesgo de importación y diseminación de la infección por SARS-CoV-2, se decidió realizar un análisis de la situación epidemiológica y de la movilidad y la migración internacional en Cuba -con énfasis en La Habana- toda vez que esta provincia es la capital del país y el epicentro de la epidemia en el territorio nacional. Las fuentes fundamentales de información proceden del Sistema de Información Estadístico Nacional, de la Oficina Nacional de Estadísticas e Información; del Ministerio de Salud Pública; del Ministerio de Trabajo y Seguridad Social; del Ministerio del Transporte; de la Dirección de Identificación, Inmigración y Extranjería y de información publicada en el sitio web Our World in Data. Los resultados fueron presentados ante las instancias de dirección del país y de la provincia de La Habana.